Population pharmacokinetics and initial dose optimization of tacrolimus in children with severe combined immunodeficiency undergoing hematopoietic stem cell transplantation - Chen, Xiao; Wang, Dongdong; Zheng, Feng; Zhai, Xiaowen; Xu, Hong; Li, Zhiping (Frontiers in Pharmacology, 2022)
The present study aimed to explore the population pharmacokinetics and initial dose optimization of tacrolimus in children with severe combined immunodeficiency (SCID) undergoing hematopoietic stem cell transplantation (HSCT). Children with SCID undergoing HSCT treated with tacrolimus were enrolled for analyzing. Population pharmacokinetics of tacrolimus was built up by nonlinear mixed effects model (NONMEM) and initial dose optimization of tacrolimus was simulated with Monte Carlo method in children weighing < 20 kg at different doses. A total of 18 children with SCID undergoing HSCT were included for analyzing, with 130 tacrolimus concentrations. Body weight was included as a covariable in the final model. Tacrolimus CL/F were 0.36-0.26 L/h/kg from body weights of 5-20 kg. Meanwhile, we simulated the tacrolimus concentrations using different body weights (5-20 kg) and different dose regimens (0.1-0.8 mg/kg/day). Finally, the initial dose regimen of 0.6 mg/kg/day tacrolimus was recommended for children with SCID undergoing HSCT whose body weights were 5-20 kg. It was the first time to establish tacrolimus population pharmacokinetics in children with SCID undergoing HSCT, in addition, the initial dose optimization of tacrolimus was recommended.